2022
DOI: 10.3389/fgene.2022.851343
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Growth-Regulating Factors-Interacting Factors in Cotton

Abstract: Growth-regulating factors-interacting factors (GIFs) are a type of transcription co-activators in plants, playing crucial roles in plants’ growth, development, and stress adaptation. Here, a total of 35 GIF genes were identified and clustered into two groups by phylogenetic analysis in four cotton genus. The gene structure and conserved domain analysis proved the conservative characteristics of GIF genes in cotton. The function of GIF genes was evaluated in two cotton accessions, Ji A-1-7 (33xi) and King, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Both GRF and GIF genes have important regulatory roles in many plant tissues and organs [ 2 , 3 , 5 , 6 , 15 18 , 20 , 23 25 ]. Similarly, we found that GRF and GIF genes are highly expressed in the tissues, organs, and developmental stages of most species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both GRF and GIF genes have important regulatory roles in many plant tissues and organs [ 2 , 3 , 5 , 6 , 15 18 , 20 , 23 25 ]. Similarly, we found that GRF and GIF genes are highly expressed in the tissues, organs, and developmental stages of most species.…”
Section: Discussionmentioning
confidence: 99%
“…GIF2 and GIF3 genes in A. thaliana can promote cell proliferation and affect leaf size [ 24 ]. Additionally, GIF genes play important roles in internode growth [ 23 ], lateral root development [ 25 ], and response to heavy metal stress [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive evaluation of the cold tolerance indices of all the tested soybean materials was conducted using the fuzzy membership function method (Luo QL et al 2023). Five cold-tolerant genotypes and ve coldsensitive genotypes were selected, and total RNA was extracted from soybean seeds subjected to 3°C lowtemperature treatment during germination for 3 days for RNA-seq analysis.…”
Section: Rna Sequencingmentioning
confidence: 99%